The Giant Protein Titin’s Role in Cardiomyopathy: Genetic, Transcriptional, and Post-translational Modifications of TTN and Their Contribution to Cardiac Disease - Tharp, Charles A.; Haywood, Mary E.; Sbaizero, Orfeo; Taylor, Matthew R. G.; Mestroni, Luisa (Frontiers in Physiology, 2019)
Dilated cardiomyopathy (DCM) is a leading cause of heart failure, sudden cardiac death and heart transplant. DCM is inherited in approximately 50% of cases, in which the most frequent genetic defects are truncation variants of the titin gene (TTNtv). TTN encodes Titin, which is the largest protein in the body and is an essential component of the sarcomere. Titin serves as a biological spring, spanning half of the sarcomere and connecting the Z-disc to the M-line, with scaffold and signaling functions. Truncations of Titin are believed to lead to either haploinsufficiency and loss-of-function, or to a “poison peptide” effect. However, other titin mechanisms are postulated to influence cardiac function including posttranslational modifications, in particular changes in titin phosphorylation that alters the stiffness of the protein, and diversity of alternative splicing that generates different titin isoforms. In this article, we review the role of TTN mutations in development of DCM, how differential expression of titin isoforms relate to DCM pathophysiology, and discuss how post translational modifications of titin can affect cardiomyocyte function. Current research efforts aim to elucidate the contribution of titin to myofibril assembly, stability, and signal transduction, and how mutant titin leads to cardiac dysfunction and human disease. Future research will need to translate this knowledge toward novel therapeutic approaches that can modulate titin transcriptional and post-translational defects to treat DCM and heart failure.